Effect of Impact Angle on Penetration of Aramid and Polyethylene Internal Ballistic Panels with the Use of 7.62 mm Lead Core, Steel Jacket Projectiles - Andrzej WRÓBLEWSKI; Monika PRACHT (Problemy Mechatroniki, 2015)
In the paper, tests results of samples of basic body armour panels are presented. The works were intended to determine the influence of projectile impact angle on the value of the ballistic limit velocity. 7.62  25 mm rounds with lead core and metal jacket bullets were used according to K2 class of the standard PN-V-87000: 2011. The tests involved two basic materials: aramid and polyethylene in several variants and different numbers of layers. Particular attention was paid to the lowest penetration velocity and bullets deformation.